GC/MS profiling of fatty acids in medically important fungi - Miketová, Petra; Jelínek, David; Khailová, Ludmila; Schram, Karl H.; Moore, Ida M.(Ki); Vytřasová, Ludmila (Univerzita Pardubice, 2004)
The application of gas chromatography/mass spectrometry (GC/MS) method was described for the generation of fatty acid profiles of medically important fungi. The composition of fatty acids was characteristic for different fungi and was used for identification and taxonomical purposes. The GC/MS methodology was shown to be suitable for diagnostic pusposes in clinical settings thanks to its sensitivity, speed and accuracy.